Inovasi Literasi Menuju Pendidikan Berkualitas melalui Program Mahasiswa KUKERTA Desa Laboy Jaya - Raja Hafiza; Ramanda Putra; Muhammad Fendrik; M. Rifaldy Efendi; Aida Sarofalina; Elva Yulvianis; Luthfia Tunnisa; Dwi Febry Koesnadi; Rizkyan Dwi Yanuar; Dela Puspita; Muhammad Ikram Syafwan; Cantica Aurelia Purba; Kartika Natalia Tumangger (Unri Conference Series: Community Engagement, 2025)
The University of Riau's 2025 Thematic Literacy Community Service Program (KUKERTA) in Laboy Jaya Village, Bangkinang District, Kampar Regency, is designed to support the achievement of Sustainable Development Goal (SDG) 4 on quality education. This village has high human resource potential but faces limitations in literacy facilities and low reading interest among the community, especially children. Through a participatory approach, students implement core programs such as library data collection, management, and services, creative literacy activities, school visits, and village-level literacy appreciation initiatives. Supporting programs include creating a village profile video, math tutoring, UMKM Go Digital training, hydroponic farming, nutrition awareness and stunting prevention campaigns, and education on the risks of online lending. The results show an increase in children's participation in literacy activities, strengthened partnerships between libraries and schools, and the creation of public spaces for cultural expression and interaction. This intervention expands the meaning of literacy from mere reading and writing to functional and transformative literacy, covering aspects of education, health, economics, and law. The sustainability of the program requires support from the village government, schools, and local communities through the provision of resources, strengthening of library institutions, and the training of literacy volunteers. This program serves as a best practice example of community-based education ecosystem development in rural areas.